2013
DOI: 10.1007/s00018-013-1450-x
|View full text |Cite
|
Sign up to set email alerts
|

CAS directly interacts with vinculin to control mechanosensing and focal adhesion dynamics

Abstract: Focal adhesions are cellular structures through which both mechanical forces and regulatory signals are transmitted. Two focal adhesion-associated proteins, Crk-associated substrate (CAS) and vinculin, were both independently shown to be crucial for the ability of cells to transmit mechanical forces and to regulate cytoskeletal tension. Here, we identify a novel, direct binding interaction between CAS and vinculin. This interaction is mediated by the CAS SRC homology 3 domain and a proline-rich sequence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 66 publications
1
62
1
Order By: Relevance
“…These cells grew in tight clusters, whereas cells expressing the most studied Cas1A or the other variants showed a high degree of cell scattering. The partial deletion of the SH3 domain in Cas1B corroborates the importance of the SH3 domain in establishing a polarized phenotype associated with cell motility and FA formation (1,42,43). Importantly, reconstitution of Cas1B in Cas Ϫ/Ϫ cells significantly reduced cell migration and invasion when compared with Cas1A cells.…”
Section: Discussionsupporting
confidence: 62%
“…These cells grew in tight clusters, whereas cells expressing the most studied Cas1A or the other variants showed a high degree of cell scattering. The partial deletion of the SH3 domain in Cas1B corroborates the importance of the SH3 domain in establishing a polarized phenotype associated with cell motility and FA formation (1,42,43). Importantly, reconstitution of Cas1B in Cas Ϫ/Ϫ cells significantly reduced cell migration and invasion when compared with Cas1A cells.…”
Section: Discussionsupporting
confidence: 62%
“…Alternatively, it was shown that the interaction of the CAS-SH3 domain with its substrates can be regulated by phosphorylation on Tyr1291213. This enables dynamically regulated changes in CAS targeting to focal adhesions, which might be critical for proper subsequent signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a third possibility is phosphorylation enhances mechanical activation and vice versa [20]. Consistent with this notion, stretching uncovers tyrosine phosphorylation sites in other proteins (i.e., p130 Cas) [23, 24] as well as vinculin binding sites in talin [25]. Thus, vinculin activation is likely to be more sophisticated than the combinatorial activation or bundle inversion models predict (Fig.…”
Section: Introductionmentioning
confidence: 91%